Ice Cream Malaysia / Nur Khairunnisa Mohd Zahid - Nur Khairunnisa, Mohd Zahid (2020)
The Nisa Ice Cream Store offer an Ice Cream Malaysia product and Service for a customer. Providing the variety different taste of Ice Cream Malaysia and create a new taste of Ice Cream Malaysia. Our client is customer identifying as Low class and Middle class who can buy our product with a low and affordable prices. Our target is to make an Ice cream who suit for everyone with different age and gender. Nisa Ice Cream Store offer a variety taste of Ice Cream Malaysia with low sugar and halal certificates. Nowadays, When a hot day people will craving a cool thing like an Ice cream. It was our advantage for our business to promote our product to the customer. Their will demand an Ice Cream and it will cause our product rise over. While currently there are many competitive businesses like our but we only business have a very special delivery services. Our business marketing strategy is to create new taste Ice Cream Malaysia to met up our customer taste. We will sold our product with low and affordable price. The quality of Ice Cream Malaysia would up to our customer standard. The Nisa Ice Cream Store is management consist of 2 clerk worker. The Nisa Ice Cream Store worker most are a very experience worker who have been in many different job and have many experience in in food industry. Some worker also did has extensive experience in finance,accounting, sales and business. 2 worker who will help the owner to arranged the business to be more successful and also it was lead by the general manager who was the owner of Nisa Ice Cream Store. Finally, The Nisa Ice Cream Store also will promote our product using the social media such as Instagram, Website, Wassap, and Facebook. We also do a promotion by selling our product in lower prices. By this many costumer will buy our product.